2015
DOI: 10.1097/aog.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Placentation

Abstract: Placental disorders such as placenta previa, placenta accreta, and vasa previa are all associated with vaginal bleeding in the second half of pregnancy. They are also important causes of serious fetal and maternal morbidity and even mortality. Moreover, the rates of previa and accreta are increasing, probably as a result of increasing rates of cesarean delivery, maternal age, and assisted reproductive technology. The routine use of obstetric ultrasonography as well as improving ultrasonographic technology allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(66 citation statements)
references
References 102 publications
(161 reference statements)
1
63
0
2
Order By: Relevance
“…Risks for abnormal placentation include factors more common among subfertile and infertile women: older maternal age, endometrial damage and uterine scarring, and short interval between prior cesarean delivery and subsequent pregnancy (56). Studies have confirmed a higher frequency of abnormal placentation in pregnancies conceived through both ovulation induction (46) and IVF (4648).…”
Section: Discussionmentioning
confidence: 99%
“…Risks for abnormal placentation include factors more common among subfertile and infertile women: older maternal age, endometrial damage and uterine scarring, and short interval between prior cesarean delivery and subsequent pregnancy (56). Studies have confirmed a higher frequency of abnormal placentation in pregnancies conceived through both ovulation induction (46) and IVF (4648).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the term "morbidly adherent placenta" (MAP) has been more frequently used to describe abnormal implantation of the placental villi into the uterine wall [2]. It is histopathological term-occurs when the placenta fails to detach from the wall of the uterus due to abnormal implantation at the basal plate [3].…”
Section: Introductionmentioning
confidence: 99%
“…10,13 Despite obstetric ultrasonography being the standard for PAS diagnosis, the reported accuracy of ultrasonography varies greatly between facilities, experts and even nations. 14,15 Magnetic resonance imaging (MRI) is sometimes used but has more variable accuracy, with higher costs and fewer radiology experts in PAS. 14 Unfortunately, disease severity can often only be assessed definitively at the time of surgery and ultimately diagnosed by histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Magnetic resonance imaging (MRI) is sometimes used but has more variable accuracy, with higher costs and fewer radiology experts in PAS. 14 Unfortunately, disease severity can often only be assessed definitively at the time of surgery and ultimately diagnosed by histopathology. Additional methods to evaluate the presence and/or severity of disease prior to surgery are critical for improving maternal outcomes.…”
Section: Introductionmentioning
confidence: 99%